A de novo missense mutation in the inositol 1, 4, 5‐triphosphate receptor type 1 gene causing severe pontine and cerebellar hypoplasia: Expanding the phenotype of ITPR1‐related spinocerebellar ataxia's. Issue 1 (9th November 2016) - van Dijk, Tessa; Barth, Peter; Reneman, Liesbeth; Appelhof, Bart; Baas, Frank; Poll‐The, Bwee Tien
Abstract : We report a de novo missense mutation (c.7649T>A) in the inositol, 1, 4, 5 triphosphate receptor type 1 ( ITPR1 ) gene in a patient with severe pontocerebellar hypoplasia. The mutation results in an amino acid substitution of a highly conserved isoleucine by asparagine (p. I2550N) in the transmembrane domain. Mutations and deletions of the ITPR1 gene are associated with several types of autosomal dominant spinocerebellar ataxia, varying in age of onset and severity. Patients have signs of cerebellar ataxia and at most, a mild cerebellar atrophy on MRI. In contrast, the patient we report here has profound cerebellar and pontine hypoplasia. Our finding therefore further expands the spectrum of ITPR1 ‐related ataxias. © 2016 Wiley Periodicals, Inc.